Positive electrode material capable of resisting surface element segregation, preparation method of positive electrode material and sodium ion battery

By doping specific bulk-phase doping elements in the positive electrode material of sodium ion battery and forming a cladding layer, the problem of surface transition metal element segregation is solved, and the performance of the battery is significantly improved, including capacity, rate performance and cycling performance.

CN119674000APending Publication Date: 2025-03-21LIYANG HINA BATTERY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411830695.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-12
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The surface transition metal element segregation in sodium ion batteries is severely hindering the transfer kinetics of sodium ions, resulting in accelerated capacity attenuation, reduced rate performance and shortened cycle life.

Method used

A positive electrode material that resists segregation of surface elements is used, which consists of a matrix material and a cladding layer. The chemical formula of the matrix material is NaiCuxNiyMnzAqO2. By doping specific bulk-phase doping elements, RA/RCNM = 0.9~1.1 and θCNM/θA = 0.85~1.0 are satisfied, and the charges are balanced and the uneven distribution of elements is reduced. At the same time, the cladding layer forms a stable passivation layer to reduce the erosion of the material by the electrolyte.

Benefits of technology

It effectively reduces the segregation phenomenon of surface elements, improves the capacity, rate performance, energy density and circulation performance of the positive electrode material, making the charging and discharge speed of sodium ion batteries fast and the circulation performance is excellent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674000A_ABST
    Figure CN119674000A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of sodium ion battery positive electrode materials, in particular to a positive electrode material capable of resisting surface element segregation, a preparation method of the positive electrode material and a sodium ion battery. The surface element segregation resistant positive electrode material comprises a NaiCuxNiyMnzAqO2 base material and a coating layer, wherein x is greater than or equal to 0.05 and less than or equal to 0.15, y is greater than or equal to 0.35 and less than or equal to 0.45, z is greater than or equal to 0.35 and less than or equal to 0.45, q is greater than or equal to 0.05 and less than or equal to 0.15, and A is at least two bulk phase doped elements; in the matrix material, the weighted average ion radius of the bulk phase doping element A is RA, the weighted average ion radius of the copper, nickel and manganese elements is RCNM, the weighted average valence state of the bulk phase doping element A is theta A, the weighted average valence state of the copper, nickel and manganese elements is theta CNM, and RA / RCNM = 0.9-1.1 and theta CNM / theta A = 0.85-1.0 are satisfied. Transition metal elements on the surface of the positive electrode material are not easy to segregate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of positive electrode materials for sodium ion batteries, and in particular to a positive electrode material resistant to surface element segregation and a preparation method thereof, and a sodium ion battery. Background Art

[0002] With the continuous development of energy storage technology, sodium-ion batteries have become one of the hot topics in the current battery research field due to their abundant resources and relatively low cost. However, in the practical application of sodium-ion batteries, there are still many challenges, among which the segregation of surface transition metal elements has a serious negative impact on battery performance.

[0003] In terms of electrochemical performance, the segregation of transition metal elements on the surface seriously hinders the transport dynamics of sodium ions. Sodium ions need to be quickly embedded and extracted in the electrode material during the battery charging and discharging process to achieve energy storage and release. With surface element segregation, charge transfer becomes uneven, element interactions change, and side reactions increase, which leads to accelerated capacity decay. At the same time, the rate performance is also greatly reduced, which cannot meet the needs of fast charging and discharging.

[0004] In terms of structural stability, surface transition element segregation will aggravate local stress concentration. The embedding and extraction process of sodium ions is accompanied by complex phase changes, and the structure of the material will change, and element segregation makes this structural change more uneven. Local stress concentration destroys the integrity of the crystal structure, accelerates the aging and damage of the electrode material, and thus shortens the cycle life of the battery.

[0005] In addition, surface transition element segregation will catalyze side reactions between the electrolyte and the material, increase interfacial impedance, and reduce energy conversion efficiency.

[0006] In summary, surface transition metal element segregation is one of the key issues restricting the performance improvement and widespread application of sodium-ion batteries.

[0007] In view of this, the present invention is proposed. Summary of the invention

[0008] The first purpose of the present invention is to provide a positive electrode material that is resistant to surface element segregation, which can effectively reduce the phenomenon of surface transition metal element segregation and avoid the negative impact of the surface transition metal element segregation problem on battery performance.

[0009] The second object of the present invention is to provide a method for preparing the above-mentioned positive electrode material that is resistant to surface element segregation. The method is simple to operate, and the transition metal elements on the surface of the prepared positive electrode material are not easily segregated.

[0010] The third object of the present invention is to provide a sodium ion battery having high capacity, good rate performance, high energy density, excellent cycle performance and fast charge and discharge speed.

[0011] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0012] The present invention first provides a positive electrode material resistant to surface element segregation, comprising a base material and a coating layer coated on the surface of the base material; the chemical formula of the base material is Na i Cu x Ni y Mn z A q O2; wherein 0.85≤i≤1.0, 0.05≤x≤0.15, 0.35≤y≤0.45, 0.35≤z≤0.45, 0.05≤q≤0.15, x+y+z+q=1, A is a bulk doping element, and A includes at least two elements; in the matrix material, the weighted average ionic radius of the bulk doping element A is R A , the weighted average ionic radius of Cu, Ni and Mn elements is R CNM , satisfying R A / R CNM =0.9~1.1; In the matrix material, the weighted average valence state of the bulk doping element A is θ A , the weighted average valence state of Cu, Ni and Mn elements is θ CNM , satisfying θ CNM / θ A =0.85~1.0.

[0013] Furthermore, the A includes at least two elements of Mg, Al, Ca, Ti and Zn.

[0014] Furthermore, the A is Al element and Ti element.

[0015] Furthermore, the surface coating elements in the coating layer include alkali metal coating elements, non-metal coating elements and strong bond energy coating elements.

[0016] Furthermore, the alkali metal coating element includes at least one of Li, Mg, Al and Ca.

[0017] Furthermore, the non-metallic coating element includes at least one of B, F and P.

[0018] Furthermore, the strong bond energy coating element includes at least one of Zr and Y.

[0019] Furthermore, the coating layer also includes a transition metal coating element, and the transition metal coating element includes at least one of Co and Zn.

[0020] Furthermore, the surface coating elements in the coating layer are F, P, Ca, Zr and Y.

[0021] Furthermore, the ratio of the molar amount of the surface coating element in the coating layer to the total molar amount of all metal elements except Na in the base material is 0.001 to 0.01.

[0022] Furthermore, the positive electrode material is an O3 type layered oxide positive electrode material.

[0023] Furthermore, in the X-ray diffraction spectrum of the positive electrode material, the diffraction angle 2θ of the 003 characteristic diffraction peak is 16.5° to 17°, and the diffraction angle 2θ of the 104 characteristic diffraction peak is 41.5° to 42.5°.

[0024] Furthermore, the conductivity of the positive electrode material is 1×10 -6 S / cm~1×10 -4 S / cm.

[0025] Furthermore, the sodium ion diffusion coefficient of the positive electrode material is 1×10 -7 cm 2 / s~1×10 -9 cm 2 / s.

[0026] Furthermore, the TM-O interlayer spacing of the positive electrode material is

[0027] Furthermore, the particle size Dv50 of the positive electrode material is 3 μm to 7 μm.

[0028] Furthermore, the positive electrode material has a morphology of single crystal particles.

[0029] The present invention further provides a method for preparing the positive electrode material resistant to surface element segregation, comprising the following steps: mixing a sodium source, a copper-nickel-manganese precursor and a dopant containing a bulk doping element A and calcining the mixture to obtain a matrix material; in the matrix material, the weighted average ionic radius of the bulk doping element A is R A , the weighted average ionic radius of Cu, Ni and Mn elements is R CNM , the weighted average valence state of the bulk doping element A is θ A , the weighted average valence state of Cu, Ni and Mn elements is θ CNM , satisfying R A / R CNM =0.9~1.1 and θ CNM / θA =0.85~1.0; the matrix material and the coating agent are mixed and sintered to obtain the positive electrode material that is resistant to surface element segregation.

[0030] Furthermore, the sodium source includes sodium carbonate.

[0031] Furthermore, the copper-nickel-manganese precursor includes at least one of a copper-nickel-manganese hydroxide precursor, a copper-nickel-manganese carbonate precursor and a copper-nickel-manganese oxide precursor.

[0032] Furthermore, the calcination temperature is 900-1000° C., and the calcination holding time is 10-20 hours.

[0033] Furthermore, the sintering temperature is 600-900° C., and the sintering holding time is 10-20 hours.

[0034] The present invention also provides a sodium ion battery, comprising the positive electrode material resistant to surface element segregation.

[0035] Compared with the prior art, the present invention has the following beneficial effects:

[0036] (1) The positive electrode material resistant to surface crystal element segregation provided by the present invention satisfies R by doping with specific bulk phase doping elements. A / R CNM =0.9~1.1 and θ CNM / θ A =0.85~1.0, which can change the electronic distribution of the material, balance the charge and reduce the uneven distribution of elements. During the repeated insertion and extraction process of sodium ions, specific bulk doping elements will balance the charge of transition metals Cu, Ni, and Mn, adjust their coordination environment, change the interaction between atoms, and thus reduce element segregation. Make the structure of the material more uniform and reduce the local enrichment or deficiency of elements. At the same time, the coating layer forms a stable passivation layer, which can reduce the corrosion of the electrolyte to the material.

[0037] (2) The positive electrode material resistant to surface crystal element segregation provided by the present invention has a specific bulk phase doping element that regulates the interlayer spacing of transition metal-oxygen (TM-O) by reducing the inhomogeneity of the local structure, stabilizes the sodium (Na) layer under the phase transition, and can reduce the structural changes and stress accumulation caused by the repeated insertion and extraction of sodium ions.

[0038] (3) The positive electrode material resistant to surface crystal element segregation provided by the present invention has high capacity, good rate performance, high energy density and excellent cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0040] Figure 1 This is a SEM image of the positive electrode material resistant to surface element segregation prepared in Example 1 provided by the present invention;

[0041] Figure 2 The XRD diagram of the positive electrode material resistant to surface element segregation prepared in Example 1 provided by the present invention;

[0042] Figure 3 The first cycle charge and discharge curve of a battery made from the positive electrode material of Example 1 provided by the present invention. DETAILED DESCRIPTION

[0043] The technical scheme of the present invention will be clearly and completely described below in conjunction with the accompanying drawings and specific embodiments, but it will be understood by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified in the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0044] If there is no special explanation, in the present invention, "the first aspect", "the second aspect", "the third aspect", "the fourth aspect", etc. are only used for descriptive purposes and cannot be understood as indicating or implying relative importance or quantity, nor can they be understood as implicitly indicating the importance or quantity of the indicated technical features. Moreover, "the first", "the second", "the third", "the fourth", etc. only serve the purpose of non-exhaustive enumeration and description, and it should be understood that they do not constitute a closed limitation on quantity.

[0045] If there is no special explanation, the "include" and "comprising" mentioned in the present invention represent open-ended or closed-ended expressions. For example, the "include" and "comprising" may represent that other components not listed may also be included or only the listed components may be included or only the listed components may be included.

[0046] If there is no special explanation, in the present invention, "one or more" or "at least one" refers to any one, any two or more of the listed items. Among them, "several" refers to any two or more of the listed items.

[0047] In a first aspect, the present invention provides a positive electrode material resistant to surface element segregation, comprising a base material and a coating layer coated on the surface of the base material.

[0048] The chemical formula of the matrix material is Na i Cu x Ni y Mn z A q O2; wherein, 0.85≤i≤1.0, 0.05≤x≤0.15, 0.35≤y≤0.45, 0.35≤z≤0.45, 0.05≤q≤0.15, x+y+z+q=1, A is a bulk doping element, and A includes at least two metal elements.

[0049] Wherein, i includes but is not limited to any one of 0.85, 0.86, 0.88, 0.9, 0.92, 0.95, 0.98, 1.0 or any range between two of them; x includes but is not limited to any one of 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15 or any range between two of them; y includes but is not limited to 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0 .43, 0.44, 0.45 or any range between them; z includes but is not limited to any one of 0.35, 0.36, 0.37, 0.38, 0.39, 0.40, 0.41, 0.42, 0.43, 0.44, 0.45 or any range between them; q includes but is not limited to any one of 0.05, 0.06, 0.07, 0.08, 0.09, 0.10, 0.11, 0.12, 0.13, 0.14, 0.15 or any range between them.

[0050] In the matrix material, the weighted average ionic radius of the bulk doping element A is R A , the weighted average ionic radius of Cu, Ni and Mn elements is R CNM , satisfying R A / R CNM =0.9~1.1. Among them, R A / R CNM The value of includes, but is not limited to, any one of 0.90, 0.91, 0.93, 0.95, 0.98, 1.0, 1.02, 1.05, 1.06, 1.08, 1.1, or a range of values ​​between any two of them.

[0051] That is, RA =(ionic radius of the first doping element × molar fraction of the first doping element in all metal elements except Na + ionic radius of the second doping element × molar fraction of the second doping element in all metal elements except Na +…+ionic radius of the nth doping element × molar fraction of the nth doping element in all metal elements except Na) / (molar fraction of the first doping element in all metal elements except Na + molar fraction of the second doping element in all metal elements except Na +…+molar fraction of the nth doping element in all metal elements except Na).

[0052] R CNM =(ionic radius of Cu element × molar proportion of Cu element in all metal elements except Na + ionic radius of Ni element × molar proportion of Ni element in all metal elements except Na + ionic radius of Mn element × molar proportion of Mn element in all metal elements except Na) / (molar proportion of Cu element in all metal elements except Na + molar proportion of Ni element in all metal elements except Na + molar proportion of Mn element in all metal elements except Na).

[0053] That is, the weight of the weighted average ionic radius is the molar proportion of the corresponding doping element in all metal elements except Na.

[0054] In the matrix material, the weighted average valence state of the bulk doping element A is θ A , the weighted average valence state of Cu, Ni and Mn elements is θ CNM , satisfying θ CNM / θ A =0.85~1.0. Among them, θ CNM / θ A The value of includes, but is not limited to, any one of 0.85, 0.86, 0.88, 0.90, 0.92, 0.93, 0.95, 0.98, 1.0, or a range of values ​​between any two of them.

[0055] That is, θ A =(ionic valence of the first doping element × the molar proportion of the first doping element in all metal elements except Na + ionic valence of the second doping element × the molar proportion of the second doping element in all metal elements except Na +…+ionic valence of the nth doping element × the molar proportion of the nth doping element in all metal elements except Na) / (molar proportion of the first doping element in all metal elements except Na + molar proportion of the second doping element in all metal elements except Na +…+molar proportion of the nth doping element in all metal elements except Na).

[0056] θ CNM=(ionic valence of Cu element × molar proportion of Cu element in all metal elements except Na + ionic valence of Ni element × molar proportion of Ni element in all metal elements except Na + ionic valence of Mn element × molar proportion of Mn element in all metal elements except Na) / (molar proportion of Cu element in all metal elements except Na + molar proportion of Ni element in all metal elements except Na + molar proportion of Mn element in all metal elements except Na).

[0057] That is, the weight of the weighted average valence state is the molar proportion of the corresponding doping element in all metal elements except Na.

[0058] The present invention provides a high-performance sodium ion battery positive electrode material that resists surface crystal element segregation, and satisfies R A / R CNM =0.9~1.1 and θ CNM / θ A =0.85~1.0, which can change the electronic distribution of the material, balance the charge and reduce the uneven distribution of elements. During the repeated insertion and extraction of sodium ions, specific bulk doping elements will balance the charge of transition metals Cu, Ni, and Mn, adjust their coordination environment, change the interaction between atoms, and reduce element segregation. This makes the material structure more uniform and reduces the enrichment or loss of local elements.

[0059] At the same time, specific bulk doping elements can regulate the interlayer spacing of transition metal-oxygen (TM-O) by reducing the inhomogeneity of the local structure, stabilizing the sodium (Na) layer under the phase transition, and alleviating the structural changes and stress accumulation caused by the repeated insertion and extraction of sodium ions.

[0060] Specifically, in terms of ionic radius: when a specific bulk doping element is introduced, if its ionic radius is close to the ionic radius of the replaced main element, it will not cause excessive lattice distortion in the lattice, so during the sodium ion insertion and extraction process, it can reduce the inhomogeneity caused by local structural changes. In terms of ionic valence: high-valence doping elements will attract electrons, causing the electron cloud distribution of the TM-O bond to change, thereby adjusting the interlayer spacing of TM-O. The inventors found that when the transition metal is maintained near the +3 valence, the interlayer spacing is stable, and the actual Na content of the material is stable. The actual Na content is the Na content of the material that can participate in the electrochemical reaction. Therefore, the present invention controls R A / R CNM =0.9~1.1 and θ CNM / θ A =0.85~1.0, improving the electrochemical performance of the positive electrode material.

[0061] In addition, the coating layer forms a stable passivation layer, which can reduce the corrosion of the electrolyte to the material.

[0062] Therefore, the positive electrode material provided by the present invention can effectively reduce the surface element segregation phenomenon, and the positive electrode material has high capacity, good rate performance, high energy density and excellent cycle performance.

[0063] In some specific embodiments, the A includes at least two elements of Mg, Al, Ca, Ti and Zn, for example, two, three, four or five thereof.

[0064] In some specific embodiments, the A is Al element and Ti element.

[0065] In some specific embodiments, the surface coating elements in the coating layer include alkali metal coating elements, non-metal coating elements and strong bond energy coating elements. Using these three types of surface coating elements at the same time is conducive to further improving the capacity, rate performance and cycle performance of the positive electrode material.

[0066] In some specific embodiments, the alkali metal coating element includes at least one of Li, Mg, Al and Ca. Among them, the Li element can improve the Na + Transport kinetics, Mg, Al, and Ca form a stable passivation layer to prevent direct contact between the material and the electrolyte and reduce the occurrence of side reactions.

[0067] In some specific embodiments, the non-metal coating element includes at least one of B, F and P. The non-metal coating element can adjust the charge distribution on the surface of the material.

[0068] In some specific embodiments, the strong bond energy coating element includes at least one of Zr and Y. Among them, zirconium and yttrium have relatively high bond energy, which can enhance the structural stability of the material coating layer.

[0069] In some specific embodiments, the coating layer further includes a transition metal coating element, and the transition metal coating element includes at least one of Co and Zn. Co and Zn interact with HF in the electrolyte to reduce electrolyte corrosion.

[0070] In some specific embodiments, the surface coating elements in the coating layer are F, P, Ca, Zr and Y. This is conducive to further improving the electrochemical performance of the positive electrode material.

[0071] In some specific embodiments, the ratio of the molar amount of the surface coating element to the total molar amount of all metal elements in the matrix material except Na is 0.001 to 0.01, including but not limited to any one of 0.001, 0.002, 0.003, 0.004, 0.005, 0.006, 0.007, 0.008, 0.009, 0.01 or a range between any two of them.

[0072] In some specific embodiments, the positive electrode material is an O3-type layered oxide positive electrode material.

[0073] In some specific embodiments, in the X-ray diffraction pattern of the positive electrode material, the diffraction angle 2θ of the 003 characteristic diffraction peak is 16.5° to 17°, including but not limited to any one of 16.5°, 16.6°, 16.7°, 16.8°, 16.9°, and 17°, or the range between any two of them; the diffraction angle 2θ of the 104 characteristic diffraction peak is 41.5° to 42.5°, including but not limited to any one of 41.5°, 41.6°, 41.7°, 41.8°, 41.9°, 42°, 42.1°, 42.2°, 42.3°, 42.4°, and 42.5°, or the range between any two of them.

[0074] In some specific embodiments, the conductivity of the positive electrode material is 1×10 -6 S / cm~1×10 -4 S / cm; including but not limited to 1×10 -6 S / cm, 3×10 -6 S / cm, 5×10 -6 S / cm, 8×10 -6 S / cm, 1×10 -5 S / cm, 3×10 -5 S / cm, 5×10 -5 S / cm, 8×10 -5 S / cm, 1×10 -4 S / cm, or a range of values ​​between any two.

[0075] In some specific embodiments, the sodium ion diffusion coefficient of the positive electrode material is 1×10 -7 cm 2 / s~1×10 -9 cm 2 / s; but not limited to 1×10 -7 cm 2 / s, 3×10 -7 cm 2 / s, 5×10 -7 cm 2 / s, 8×10 -7 cm 2 / s, 1×10 - 8 cm 2 / s, 3×10 -8 cm 2 / s, 5×10 -8 cm 2 / s, 8×10 -8 cm 2 / s, 1×10 -9 cm 2 / s or any point value or range value between any two of them. The positive electrode material has a fast charge and discharge speed.

[0076] In some specific embodiments, the TM-O interlayer spacing of the positive electrode material is Including but not limited to Any point value in or any range of values ​​between them.

[0077] Among them, the TM-O interlayer spacing refers to the distance between transition metal ions (TM) and oxygen ions (O), which directly affects the migration path and rate of sodium ions in layered materials, and thus affects the charge and discharge performance of the battery.

[0078] In some specific embodiments, the TM-O interlayer spacing is obtained by refinement of XRD.

[0079] In some specific embodiments, the particle size Dv50 of the positive electrode material is 3 μm to 7 μm, including but not limited to any point value of 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, or a range value between any two of them.

[0080] In some specific embodiments, the positive electrode material is in the form of single crystal particles.

[0081] In a second aspect, the present invention provides a method for preparing the positive electrode material resistant to surface element segregation, comprising the following steps:

[0082] The sodium source, copper-nickel-manganese precursor and dopant containing bulk doping element A are mixed and calcined to obtain a matrix material; during this process, the raw materials undergo solid-phase chemical reactions, causing the crystals to gradually grow and form a stable positive electrode material structure.

[0083] Among them, in the matrix material, the weighted average ionic radius of the bulk doping element A is R A , the weighted average ionic radius of Cu, Ni and Mn elements is R CNM , the weighted average valence state of the bulk doping element A is θ A, the weighted average valence state of Cu, Ni and Mn elements is θ CNM , satisfying R A / R CNM =0.9~1.1 and θ CNM / θ A =0.85-1.0. Preferably, the bulk doping element A includes at least two elements selected from Mg, Al, Ca, Ti and Zn.

[0084] The base material and the coating agent are mixed and sintered to obtain the positive electrode material resistant to surface element segregation. In this process, the coating agent is combined with the surface of the material particles through a solid phase chemical reaction.

[0085] The method for preparing the positive electrode material resistant to surface element segregation provided by the present invention is a high-temperature solid phase reaction. The method is simple to operate, easy to implement, and suitable for mass production. Moreover, the transition metal elements on the surface of the positive electrode material prepared by the method are not prone to segregation.

[0086] In some specific embodiments, the sodium source includes but is not limited to sodium carbonate.

[0087] In some specific embodiments, the copper-nickel-manganese precursor includes at least one of a copper-nickel-manganese hydroxide precursor, a copper-nickel-manganese carbonate precursor, and a copper-nickel-manganese oxide precursor.

[0088] In some specific embodiments, the calcination temperature is 900-1000°C, including but not limited to any one of 900°C, 910°C, 930°C, 950°C, 980°C, 1000°C or a range between any two of them; the calcination holding time is 10-20h, including but not limited to any one of 10h, 12h, 15h, 18h, 20h or a range between any two of them.

[0089] In some specific embodiments, the sintering temperature is 600-900°C, including but not limited to any one of 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C or a range between any two of them; the sintering holding time is 10-20h, including but not limited to any one of 10h, 12h, 15h, 18h, 20h or a range between any two of them.

[0090] In some specific embodiments, after the calcination, the cooled raw material is crushed and ground.

[0091] In some specific implementations, the cooled raw materials are crushed and ground after sintering.

[0092] In some specific embodiments, the dopant containing the bulk doping element A includes a compound containing the element A, such as an oxide, a carbonate, a nitrate, etc., but is not limited thereto.

[0093] In some specific embodiments, the coating agent includes a compound containing a surface coating element, such as an oxide, a carbonate, a nitrate, etc., but is not limited thereto.

[0094] In a third aspect, the present invention provides a sodium ion battery comprising the positive electrode material that is resistant to surface element segregation.

[0095] The sodium ion battery has high capacity, good rate performance, high energy density, excellent cycle performance and fast charge and discharge speed.

[0096] Wherein, the sodium ion battery comprises a positive electrode sheet, and the positive electrode sheet comprises the above-mentioned positive electrode material that is resistant to surface element segregation.

[0097] Optionally, the positive electrode sheet further includes a binder and / or a conductive agent, which is not limited in the present invention.

[0098] Optionally, the sodium ion battery further includes a negative electrode sheet, a separator and an electrolyte, which is not limited in the present invention.

[0099] The embodiments of the present invention will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. If no specific conditions are specified in the examples, the conditions are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be obtained commercially.

[0100] Example 1

[0101] The positive electrode material for resisting surface element segregation provided in this embodiment comprises a base material and a coating layer coated on the surface of the base material; wherein the chemical formula of the base material is Na i Cu 0.05 Ni 0.40 Mn 0.40 Al 0.0333 Ti 0.0833 Zn 0.0333 O2; the surface coating elements in the coating layer are Mg, Al, Ca, F and P elements; the ratio of the molar amount of the surface coating elements in the coating layer to the total molar amount of all metal elements in the base material except Na is 0.008.

[0102] The method for preparing the positive electrode material resistant to surface element segregation provided in this embodiment includes:

[0103] (1) Raw material mixing: Sodium carbonate, Cu 0.05 Ni0.40 Mn 0.40 (OH) 1.8 The precursor, aluminum oxide, titanium oxide and zinc oxide are fully mixed, and then the mixed raw materials are placed in a high-temperature furnace and calcined at 950° C. for 12 hours. The calcined product is then crushed and ground to obtain a matrix material.

[0104] (2) The base material prepared in step (1) is fully mixed with magnesium oxide, aluminum oxide, calcium oxide, NaF and NH4H2PO4, and then the mixed material is placed in a high-temperature furnace and sintered at 700°C for 12 hours. The sintered product is then crushed and ground to obtain a positive electrode material that is resistant to surface element segregation.

[0105] The SEM image of the positive electrode material resistant to surface element segregation prepared in this embodiment is shown in Figure 1 The XRD pattern of the positive electrode material resistant to surface element segregation prepared in this embodiment is shown in Figure 2 It can be seen that the positive electrode material is an O3-type layered oxide positive electrode material, and the morphology of the positive electrode material is a single crystal particle.

[0106] Example 2-Example 9

[0107] The positive electrode materials resistant to surface element segregation of Examples 2 to 9 differ from the positive electrode material of Example 1 in that the base materials are different and the coating layers are different, as shown in Tables 1 and 4 for details. The preparation methods of each example refer to Example 1 (adaptively adjusting the type of dopant (all are oxides) and its dosage, the type of coating agent (the metal coating elements are all oxides, F is NaF, P is NH4H2PO4, and B is B2O3) and its dosage).

[0108] The positive electrode materials prepared in each embodiment are all O3-type layered oxide positive electrode materials, and the morphology is all single crystal particles.

[0109] Comparative Example 1-Comparative Example 9

[0110] The difference between the positive electrode materials of Comparative Examples 1 to Comparative Examples 9 and the positive electrode material of Example 1 is that the base materials are different (the coating layers are the same as those in Example 1), as shown in Table 1. The preparation methods of each comparative example refer to Example 1 (adaptively adjusting the type of dopant (all oxides) and its amount).

[0111] Comparative Example 10

[0112] The difference between the positive electrode material of comparative example 10 and the positive electrode material of embodiment 1 is that the base material is different and does not contain a coating layer, as shown in Table 1. The preparation method of this comparative example refers to embodiment 1 (adaptively adjusting the type of dopant (all oxides) and its amount).

[0113] Comparative Example 11-Comparative Example 15

[0114] The difference between the positive electrode materials of Comparative Examples 1 to Comparative Examples 15 and the positive electrode material of Example 1 is that the coating layers are different (the base material is the same as that of Example 1), as shown in Table 4 for details. The preparation methods of each comparative example refer to Example 1 (adaptively adjusting the type of coating agent (the metal coating elements are all oxides, F is NaF, P is NH4H2PO4, and B is B2O3) and its amount).

[0115] The molar percentages of the elements in the chemical formula of the matrix materials in the positive electrode materials of the embodiments and comparative examples (i.e., the values ​​of the subscripts i, x, y, z, q of the elements) are shown in Table 1.

[0116] Table 1 Molar percentage of each element in the chemical formula of the matrix material of each embodiment and each comparative example

[0117]

[0118] The ionic radius and ionic valence of Cu, Ni, Mn, Mg, Al, Ca, Ti and Zn elements are shown in Table 2.

[0119] Table 2 Ionic radius and ionic valence of each element

[0120]

[0121]

[0122] In the matrix material of the positive electrode materials in each embodiment and each comparative example, R A (weighted average ionic radius of bulk doping element A), R CNM (weighted average ionic radius of Cu, Ni and Mn elements) and R A / R CNM The value of θ CNM (weighted average valence of Cu, Ni and Mn elements), θ A (weighted average valence state of bulk doping element A) and θ CNM / θ A The values ​​are shown in Table 3.

[0123] Table 3 R in various matrix materials A , R CNM , R A / R CNM ,θ CNM ,θ A ,θ CNM / θ A

[0124]

[0125] The coating elements and their molar proportions (the ratio of the molar amount of the surface coating element to the total molar amount of all metal elements except Na in the base material) of the coating layer in the positive electrode materials of each embodiment and each comparative example are shown in Table 4.

[0126] Table 4 Coating elements and their molar proportions in each coating layer

[0127]

[0128] Furthermore, the physical and chemical properties of the positive electrode materials of Examples 1 to 9 and Comparative Examples 1 to 10 were tested, and the results are shown in Table 5. Wherein, 003 characteristic peak 2θ and 104 characteristic peak 2θ refer to the diffraction angle of 003 characteristic diffraction peak and the diffraction angle of 104 characteristic diffraction peak in the X-ray diffraction spectrum of the positive electrode material. E-06 refers to ×10 -6 , E-05 finger × 10 -5 , E-07 finger × 10 -7 , E-08 finger × 10 -8 , E-09 finger × 10 -9 For example, 8.00E-06 means 8.00×10 -6 .

[0129] XRD tests were performed on the positive electrode materials of Examples 1 to 9 and Comparative Examples 1 to 10, and the results are shown in Table 5. The impurity peak area ratio was calculated. The impurity peak area ratio was obtained by performing peak-peak fitting on the XRD data, and the peaks corresponding to the characteristic peak angles of CuO (35° and 38°), NiO (37° and 43°) and MnO (34° and 40°) were identified as impurity peaks, and the impurity peak area ratio = impurity peak area / total peak area.

[0130] Table 5 Performance indicators of various positive electrode materials

[0131]

[0132] It can be seen from Table 1, Table 3 and Table 5 that Examples 1 to 9 meet R A / R CNM =0.9~1.1 and θ CNM / θ A =0.85~1.0, the test results of various parameters are better, with suitable 003 characteristic peak 2θ, 104 characteristic peak 2θ, conductivity, sodium ion diffusion coefficient, TM-O interlayer spacing and particle size Dv50, which is beneficial to improve the capacity, rate performance, energy density and cycle performance of the positive electrode material.

[0133] At the same time, embodiments 1 to 9 of the present invention satisfy R by doping specific bulk doping elements. A / R CNM =0.9~1.1 and θ CNM / θ A =0.85~1.0, which can effectively reduce surface element segregation (the area ratio of impurity peaks is low).

[0134] The doping elements in Comparative Example 1 do not satisfy R A / R CNM = 0.9 to 1.1, the charge of transition metals Cu, Ni, and Mn and their coordination environments cannot be balanced, and the material elements are severely segregated, which can be verified from the impurity peak area ratio (the impurity peak area ratio is significantly increased). The same is true for the other comparative examples 2 to 10, because they do not meet R A / R CNM =0.9~1.1 or θ CNM / θ A =0.85~1.0, or there is no coating layer, and the surface element segregation is serious (the area of ​​the impurity peak accounts for a high proportion).

[0135] Furthermore, the positive electrode materials of Examples 1 to 9 and Comparative Examples 11 to 15 were respectively made into batteries, and the electrochemical performance tests were performed. The results are shown in Table 6.

[0136] The preparation method of the battery is as follows: the positive electrode materials prepared in each embodiment and each comparative example are used as active materials, 0.45g of active materials, 0.025g of SP (SP is specifically Swiss high conductive carbon black SUPER P) and 0.25g of polyvinylidene fluoride glue (mass percentage 10%, solute is SOLVAY PVDF5130, solvent is NMP) are uniformly mixed, and then NMP is added to make a viscous glue. The glue is coated on an aluminum foil with a thickness of 16μm, and then baked in a vacuum drying oven at 120°C for 12h to obtain a positive electrode sheet with an active material surface density of 5mg / cm 2 . A 300μm thick sodium metal sheet (Aladdin) was used as the counter electrode, a 675μm thick glass fiber (Waterman) was used as the diaphragm, and a 1mol / L NaPF6 solution (the solvent was a mixture of EC and DMC in a volume ratio of 1:1) was used as the electrolyte. A 2032 button cell was assembled in an Ar atmosphere protection glove box. Afterwards, at 25°C, each battery was charged to 4.5V at a constant current of 0.1C (nominal specific capacity 100mAh / g), and then charged at a constant voltage until the current was less than or equal to 0.01mA, then left to stand for 5 minutes, and then discharged to 1.5V at a constant current of 0.1C. This was the activation process of the battery, and subsequent tests were performed after activation.

[0137] The electrochemical performance test method is as follows:

[0138] The test method for the first-cycle discharge capacity is as follows: (1) At 25°C, charge the battery at a constant current of 0.1C to 4.2V, then charge at a constant voltage until the current is less than or equal to 0.01mA, then let it stand for 5 minutes, and then discharge at a constant current of 0.1C to 2.5V. The discharge capacity at this time is the first-cycle discharge capacity.

[0139] The test method of cycle retention rate is as follows: (1) At 25°C, charge the battery to 4.2V at 0.5C constant current, then charge at constant voltage until the current is less than or equal to 0.01mA, then let it stand for 5 minutes, then discharge to 2.5V at 0.5C constant current, then let it stand for 5 minutes. This is a charge and discharge cycle. The discharge capacity is recorded as the discharge capacity of the first cycle at the 0.5C charge and discharge rate of the battery. Perform 100 cycles of charge and discharge test according to the above method, record the discharge capacity of the 100th cycle, and then calculate the cycle retention rate as the discharge capacity of the 100th cycle / discharge capacity of the first cycle × 100%.

[0140] The test method of rate discharge is as follows: at 25°C, charge the battery to 4.2V at 0.1C constant current, then charge at constant voltage until the current is less than or equal to 0.01mA, then let it stand for 5 minutes, and then discharge to 2.5V at 2C constant current. The discharge capacity / charge capacity × 100% is the rate discharge.

[0141] Table 6 Electrochemical performance indicators of various positive electrode materials

[0142]

[0143] Figure 3 This is the first cycle charge and discharge curve of the battery made from the positive electrode material of Example 1.

[0144] It can be seen from Table 4 and Table 6 that Examples 1 to 9 use specific surface coating elements to effectively improve the rate performance and cycle performance of the material. However, the discharge specific capacity, rate discharge or cycle retention rate of Comparative Examples 11 to 15 are significantly lower than those of Example 1.

[0145] This shows that by using three types of surface coating elements, namely alkali metal coating elements, non-metallic coating elements and strong bond energy coating elements, the coating layer can play an effective role and can further improve the discharge specific capacity, rate performance and cycle retention rate of the positive electrode material.

[0146] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.

Claims

1. A positive electrode material resistant to surface element segregation, characterized in that: It comprises a base material and a coating layer coated on the surface of the base material; The chemical formula of the matrix material is Na i Cu x Ni y Mn z A q O2; wherein 0.85≤i≤1.0, 0.05≤x≤0.15, 0.35≤y≤0.45, 0.35≤z≤0.45, 0.05≤q≤0.15, x+y+z+q=1, A is a bulk doping element, and A includes at least two elements; In the matrix material, the weighted average ionic radius of the bulk doping element A is R A , the weighted average ionic radius of Cu, Ni and Mn elements is R CNM , satisfying R A / R CNM =0.9~1.1; In the matrix material, the weighted average valence state of the bulk doping element A is θ A , the weighted average valence state of Cu, Ni and Mn elements is θ CNM , satisfying θ CNM / θ A =0.85~1.

0.

2. The positive electrode material resistant to surface element segregation according to claim 1, characterized in that: Meet one of the following conditions: (1) A includes at least two elements selected from the group consisting of Mg, Al, Ca, Ti and Zn; (2) A is Al element and Ti element.

3. The positive electrode material resistant to surface element segregation according to claim 1, characterized in that: The surface coating elements in the coating layer include alkali metal coating elements, non-metal coating elements and strong bond energy coating elements; Wherein, the alkali metal coating element includes at least one of Li, Mg, Al and Ca; The non-metallic coating element includes at least one of B, F and P; The strong bond energy coating element includes at least one of Zr and Y.

4. The positive electrode material resistant to surface element segregation according to claim 3, characterized in that: The coating layer also includes a transition metal coating element, and the transition metal coating element includes at least one of Co and Zn.

5. The positive electrode material resistant to surface element segregation according to claim 3, characterized in that: The surface coating elements in the coating layer are F, P, Ca, Zr and Y.

6. The positive electrode material resistant to surface element segregation according to any one of claims 1 to 5, characterized in that: The ratio of the molar amount of the surface coating element in the coating layer to the total molar amount of all metal elements except Na in the base material is 0.001 to 0.

01.

7. The positive electrode material resistant to surface element segregation according to claim 1, characterized in that: At least one of the following conditions is met: (1) The positive electrode material is an O3-type layered oxide positive electrode material; (2) In the X-ray diffraction spectrum of the positive electrode material, the diffraction angle 2θ of the 003 characteristic diffraction peak is 16.5° to 17°, and the diffraction angle 2θ of the 104 characteristic diffraction peak is 41.5° to 42.5°; (3) The conductivity of the positive electrode material is 1×10 -6 S / cm~1×10 -4 S / cm; (4) The sodium ion diffusion coefficient of the positive electrode material is 1×10 -7 cm 2 / s~1×10 -9 cm 2 / s; (5) The TM-O interlayer spacing of the positive electrode material is (6) The particle size Dv50 of the positive electrode material is 3 μm to 7 μm; (7) The positive electrode material has a morphology of single crystal particles.

8. The method for preparing a positive electrode material resistant to surface element segregation according to any one of claims 1 to 7, characterized in that: The steps include: A sodium source, a copper-nickel-manganese precursor and a dopant containing a bulk doping element A are mixed and calcined to obtain a matrix material; in the matrix material, the weighted average ionic radius of the bulk doping element A is R A , the weighted average ionic radius of Cu, Ni and Mn elements is R CNM , the weighted average valence state of the bulk doping element A is θ A , the weighted average valence state of Cu, Ni and Mn elements is θ CNM , satisfying R A / R CNM =0.9~1.1 and θ CNM / θ A =0.85~1.0; The base material and the coating agent are mixed and then sintered to obtain the positive electrode material resistant to surface element segregation.

9. The method for preparing a positive electrode material resistant to surface element segregation according to claim 8, characterized in that: At least one of the following conditions is met: (1) The sodium source includes sodium carbonate; (2) The copper-nickel-manganese precursor includes at least one of a copper-nickel-manganese hydroxide precursor, a copper-nickel-manganese carbonate precursor and a copper-nickel-manganese oxide precursor; (3) The calcination temperature is 900-1000° C. and the holding time is 10-20 hours; (4) The sintering temperature is 600-900°C and the holding time is 10-20h.

10. A sodium ion battery, characterized in that: The invention comprises a positive electrode material resistant to surface element segregation as claimed in any one of claims 1 to 7.